2014
DOI: 10.1111/eci.12367
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acotiamide on gastric emptying in healthy adult humans

Abstract: A single administration of 100 or 300 mg of acotiamide did not affect gastric emptying after a liquid meal in healthy adult humans. Acotiamide has profound effects on restoring delayed gastric emptying and impaired accommodation in patients with FD but may have no effect on gastric emptying in healthy subjects. Such pharmacological actions have not been observed in previous gastroprokinetic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 36 publications
4
19
0
1
Order By: Relevance
“…Interestingly, no effects were found on basal feeding and basal gastric emptying rate . In line with these results, a single dose of acotiamide did not affect gastric emptying rate after a liquid meal in healthy subjects . The results of the current study further support this suggestion, showing no changes in normal/non‐dysfunctional gastric emptying after a 3‐week treatment with acotiamide.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, no effects were found on basal feeding and basal gastric emptying rate . In line with these results, a single dose of acotiamide did not affect gastric emptying rate after a liquid meal in healthy subjects . The results of the current study further support this suggestion, showing no changes in normal/non‐dysfunctional gastric emptying after a 3‐week treatment with acotiamide.…”
Section: Discussionsupporting
confidence: 89%
“…Second, we did not measure gastric accommodation and gastric emptying. Delayed gastric emptying was improved by acotiamide in several studies of animal models and humans; however, normal or non-dysfunctional gastric emptying was unaffected by acotiamide [13,24]. In this study, we recruited normal subjects who did not report typical GERD symptoms; hence, our study could not reveal why reflux events during TLESRs were significantly reduced by acotiamide.…”
Section: Discussionmentioning
confidence: 97%
“…We showed that acotiamide significantly decreased the number of nonacid reflux events, but not acid reflux. Zai et al [24] reported that acotiamide did not affect gastric emptying in healthy subjects. On the other hand, there is no data of acotiamide on gastric accommodation in healthy subjects; we can therefore only speculate that the observed effect of acotiamide on the reduction of nonacid reflux may be through a facilitated gastric accommodation, something that should be researched in future study.…”
Section: Discussionmentioning
confidence: 99%
“…32 In another study, acotiamide or a placebo was administered orally to 12 subjects 30 min before ingestion of 400 kcal/400 mL of test meal consisting of 64.4% carbohydrate, 17.6% fat, and 18% protein, labeled with 100 mg of 13 C-sodium acetate. 33 Participants with FD symptoms or H. pylori infection were excluded. They were administered acotiamide 100 mg t.i.d.…”
Section: Advanced Clinical Studies Regarding the Effect Of Acotiamidementioning
confidence: 99%